Comparative Examination of the Competent Court in International Bankruptcy Cases with a specific Approach towards Iran’s Law - Simayi Sarraf, Hossein; Nosrati, Hussein (Opción, 2019)
One of the most important issues in cases of international bankruptcy is deter- mining a competent court. The approach of Iran’s current laws and the inter- national laws are not the same in this regard. On this basis, if any elements of bankruptcy cases exist in different countries, which court will be competent in one of these countries, and how will it be enforced in Iran’s law if it is issued in one of these courts? Based on the findings of the present study, which has been done in a descriptive analytical method, if international bankruptcy pro- ceedings are brought in Iran, determining the competent court will be based on the criteria set forth in Articles 21 and 22 of the Civil Procedure Law, but if the proceedings are brought outside of Iran, a court will be considered com- petent as the competent court for a substantive foreign prosecution, which is the center of main interests of the debtor in his area. In addition, the court located at the debtor’s establishment will be competent to deal with a foreign non-main proceedings.